HADITH ON MARRIAGE IN THE FRAME OF MEMES: A CRITICAL STUDY AND ITS POTENTIAL AS COUNSELING MATERIAL FOR THE MINISTRY OF RELIGIOUS AFFAIRS - Rahmat Alfi Syahri Marpaung; Zulfirman Manik (Jurnal Ushuluddin, 2026)
The spread of hadith content through memes on Instagram is growing rapidly and reaching millions of Indonesian Muslim users, yet it lacks adequate scientific verification mechanisms. Memes with the hashtag #hadisnikah, which contain hadiths about marriage and women, have the potential to shape public religious understanding on a massive scale without accountability. This study aims to identify patterns of understanding of hadiths about marriage in digital memes with the hashtag #hadisnikah and their implications, and to evaluate the potential of hadith memes about marriage as marriage counseling materials for religious counselors at the Ministry of Religious Affairs. This study uses a qualitative approach with a descriptive analytical content analysis method. Primary data were obtained through systematic documentation of accounts posting hadith memes on Instagram with the hashtag #hadisnikah, which were analyzed through a meta-analysis and evaluation of counseling potential. The results show that the pattern of hadith understanding that is formed tends to be textually literalist with narrative imbalances that emphasize women's obligations disproportionately compared to their rights, thus constructing an unequal gender representation. Another finding found that memes have great potential as a medium for marriage counseling if they are selected critically, integrated into Suscatin sessions, and supported by the production of officially verified hadith memes by the Ministry of Religion.